Strategi ruang terbuka hijau pemakaman di Kota Pekanbaru - Muhammad Fahrul; Yusni Ikhwan Siregar; Sukendi Sukendi (Pelantar Press, 2020)
One alternative to overcome the issue of Pekanbaru City Open Space quantity that does not meet the requirements is to reorganize the function and optimization of existing Open Space. A potential open space that has been neglected is cemetery. Cemetery are often ignored because of images related to death, whereas in addition to social functions, there are also ecological and economic functions. One form of cemetery is a public cemetery (TPU) managed by the Pekanbaru City government. Given its potential, a funeral green space strategy is needed. Strategic formulation using SWOT and priority setting using AHP. Inputs needed in the preparation of this strategy are the existing conditions and their compliance with funeral green space guidelines, people's perceptions and preferences.